Cultura informacional: proposta de integração conceitual e modelo com o foco organizacional - Leonardo Barbosa de Moraes (2013)
The study aimed, as a first step, to investigate the concept of information culture in the organizational field. Through a search in peer-reviewed publications, we identified 1495 papers classified into 25 different topics. The choice of organizational approach reduced the number of jobs to 35, 15 being empirical, which served as the basis for the initial objective. The theme of this research sought dialogued and theoretical contributions in the field of information science, beyond the fields of organization theory and information systems. The consolidation of an integrated concept of information culture had also intended to propose a model for the concept and methodology that can be used in organizational contexts for the identification and interpretation of the variables that constitute the informational culture. Procedures were used as historical and typological support for conceptual model. An empirical study was conducted to analyze the information culture of a large organization Cemig - in the light of the proposed methodology. 208 employees from different areas of the company answered the questionnaire. For the analysis of the results we used descriptive statistics and Principal Components Analysis. Data analysis identified the variables most representative of the information behaviors and values of the organization studied within each of the five categories proposed. We highlight the 'perceived usefulness of information', the 'importance of social networks', the 'proactivity', the 'control' and 'level of trusts in ICT'. It also became evident the difference in values and behaviors between officeholders and among different people with different employment time. An example was identified on the superintendents of the organization, even though a high level of confidence in technological tools, demand information products more suited to the exercise of its function. The results of this research suggest that the concept and the methodology proposed can be widely used in future research on the informational culture.